Pengaruh Brand Loyalty, Brand Association, Percevied Quality Terhadap Keputusan Menggunakan Jasa Grab ( Studi Kasus Mahasiswa S1 FEB Unisma ) - Mubarok, Moh Sahrul; Nurhajati, Nurhajati; Rahmawati, Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to analyze the influence of brand loyalty, brand association and perceived quality on purchasing decisions for Grab Services. The research was conducted using a survey method of 95 respondents using a purposive sampling technique. The data analysis method used in this research was quantitative data analysis using multiple linear regression analysis. The data test used is partial hypothesis testing (t test). The research results show that brand association has a significant positive effect on purchasing decisions, while brand loyalty and perceived quality have no significant effect. In conclusion, increasing brand association can significantly increase purchasing decisions on Grab Services, while brand loyalty and perceived quality do not have a significant influence on purchasing decisions. Keywords: Brand Loyalty, Brand Association, Perceived Quality, And Purchasing Decisions